Concrete shoes for competition: The effect of the German cement cartel on market price - Kai Hüschelrath; Kathrin Müller; Tobias Veith (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
We use publicly available price data from the German cement industry to estimate the cartelinduced price increase. We apply two different comparator-based approaches - the 'before and-after' approach and the 'difference-in-differences' approach - and especially study the impact of various assumptions on the transition period from the cartel period to the non-cartel period on the overcharge estimate. We find that the cement cartel led to price overcharges in a range from 20.3 to 26.5 percent depending on model approach and model assumptions.
Keywords: 330; antitrust policy; cartels; private enforcement; damages; overcharge; Zementindustrie; Kartell; Zement; Preis; Soziale Kosten; Schätzung; Deutschland